Credit Market Frictions and the Linkage Between Dispersion and Macro Uncertainty - Li, Jun E. (Management Science, 2025)
Cross-sectional dispersion and macro uncertainty (volatility of aggregate economic variables) are conceptually distinct. However, empirically, they both comove and are countercyclical. This paper builds a general equilibrium model and demonstrates that credit market frictions allow cross-sectional dispersion to drive time-varying macro uncertainty endogenously. In the model, as firm-level productivity becomes more dispersed, more firms are pushed to the left tail of the productivity distribution, resulting in more defaults and a depletion in aggregate net worth. This mechanism generates countercyclical leverage and aggregate volatility. The model implies that the government can inject equity in economic downturns to stabilize aggregate volatility. This paper was accepted by Lukas Schmid, finance. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.00166 .